Boosting Chickpea Production by Optimizing Inter-Row and Intrarow Spacing at Central Highlands of Ethiopia - Almaz Meseret Gezahegn; Bizuwork Tafes; Sisay Eshetu (International Journal of Agronomy)
A field experiment was conducted to determine optimum inter-row and intrarow spacing for a higher and economic yield of different chickpea varieties during 2016–2017 cropping season at Debre Zeit and Minjar. The experiment was carried out in a split-plot design replicated three times. The two varieties (Habru and Arerti) were assigned as a main plot and factorial of three inter-row spacing (20 cm, 30 cm, and 40 cm) and three intrarow spacing (5, 10, and 15 cm) as subplot treatments. The result indicated that variety and inter-row and intrarow spacing had a significant effect on yield and yield components of chickpea at both locations. Habru variety gave higher seed and biomass yield than Arerti. The highest seed and biomass yield were recorded for the intrarow and inter-row spacing range of 5–15 × 30–40 cm, respectively. Results of the partial budget analysis showed that the highest net benefit with acceptable marginal rate of return (>100%) was obtained from 10 cm × 30 cm intrarow and inter-row spacing. Therefore, 10 cm × 30 cm intrarow and inter-row spacing (330, 000 plants ha−1) can be recommended for a higher and economically optimum yield of chickpea at central highlands of Ethiopia.